Optimal timing of GnRH antagonist initiation in IVF-ET: a retrospective cohort study on advanced maternal age women - Han, Qiao-Song; Zhou, Yue; Xu, Ying; Ai, Kai-Liang; Song, Jing-Yan; Sun, Zhen-Gao (Frontiers in Endocrinology, 2024)
Background Several studies have compared the effects of fixed and flexible gonadotropin releasing hormone antagonist (GnRH-ant) protocols during in vitro fertilization and embryo transfer (IVF-ET). However, which GnRH-ant initiation strategy is better remains controversial. Moreover, no studies have assessed the optimal timing of GnRH-ant initiation in women of advanced maternal age (AMA). Methods In this retrospective cohort study, a total of 472 infertile women aged ≥ 35 years old undergoing their first IVF cycle from August 2015 to September 2021 at a tertiary academic medical center were recruited, of whom 136 followed fixed GnRH-ant protocol and 336 followed flexible GnRH-ant protocol. The primary outcomes measured were the cumulative live birth rate (CLBR) per IVF cycle and the time to live birth (TTLB) from the date of oocyte retrieval. Cox proportional models were used to calculate the hazard ratio (HR) and 95% confidence interval (CI) of CLBR regarding GnRH-ant timing. Results No significant difference in CLBR was found between the fixed and flexible GnRH-ant groups (27.9% vs 20.5%, p=0.105). The TTLB was also comparable between groups (10.56 vs 10.30 months, p=0.782). The Kaplan-Meier analysis for CLBR also showed comparable results between groups (P=0.351, HR=0.83; 95%CI: 0.56-1.23). After establishing a multiple Cox proportional hazard model, the fixed GnRH-ant group still had comparable CLBR with the flexible GnRH-ant group (HR=0.85; 95%CI: 0.53-1.38; P=0.518). Subgroup and sensitivity analyses also demonstrated similar results. Conclusion GnRH-ant protocols can be tailored to the needs of AMA women, and timing of GnRH-ant initiation can be adjusted flexibly.